The Reporting the EFL Students’ Distressing Experience in Writing a Recount Text - Widya Rizky Pratiwi; Nunung Prasetyo; Lidwina Sri Ardiasih (Universitas Muhammadiyah Enrekang, 2023)
Writing is the most complex and challenging subject. These are believed to occur because they have trouble rephrasing statements and placing suitable words, especially in writing recount text. As known, recount text has the social function of retelling events for information or entertainment. This study tried approaching the EFL students to explore deeply about their distressing experience writing a recount text. This study applied a qualitative case study approach. Six students participated in this study. The participants were selected in two stages purposely with several considerations. In the data collection, the researchers used semi-structured to elaborate data based on students’ responses. The interview questions were developed or adapted from Norrish and Richard’s opinions about the causes of writing errors. The researchers used data analysis by employing a descriptive qualitative analytic technique from describing, illustrating, and evaluating. The study found two primary reasons students make grammatical errors in their recount writing. The first cause was transferring pupils' English grammar and language structure knowledge into Indonesian. Because of this, they could not finish their papers with the correct sentence structure. In addition, the impact of the first language is due to the influence of the Indonesian system. However, intra-language also caused contributed to grammatical errors in terms of an overgeneralization, insufficient application of the rule, and ignorance of rule restriction. In other words, intra-languages and inter-language information were the primary cause of the grammatical errors. For this reason, it suggested that all teachers do corrections about grammatical errors made by students that need more practice and an explanation, as well as comments regarding whether students successfully learned English writing material.